2011
DOI: 10.1177/1559827610392493
|View full text |Cite
|
Sign up to set email alerts
|

Body Composition of Young Athletes

Abstract: Systematic training for sport may be an additional factor, among others, that infl uences components and relationships among the components of body composition.Abstract: Absolute and relative components of body mass are a primary focus in studies of body composition. Components change with growth and maturation, requiring care in selecting methods of assessment in children and adolescents. Although sex differences are apparent in fat-free mass (FFM), fat mass (FM), and relative fatness (% Fat) during childhood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
78
1
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(91 citation statements)
references
References 91 publications
5
78
1
7
Order By: Relevance
“…The main finding of this study was that the percentage of fat mass was significantly lower in the posttest in SB and SG, and it might be due to the training volume that the pubertal athletes had completed. Those results were consistent with the findings of other authors that observed a lower adiposity and lower percentage of fat mass in young athletes (Strong et al;Malina, 2009;Malina & Geithner;Slater et al). The sport and physical activity are seen as important for long-term benefits in body composition (Janz et al, 2009 Table II.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The main finding of this study was that the percentage of fat mass was significantly lower in the posttest in SB and SG, and it might be due to the training volume that the pubertal athletes had completed. Those results were consistent with the findings of other authors that observed a lower adiposity and lower percentage of fat mass in young athletes (Strong et al;Malina, 2009;Malina & Geithner;Slater et al). The sport and physical activity are seen as important for long-term benefits in body composition (Janz et al, 2009 Table II.…”
Section: Discussionsupporting
confidence: 94%
“…Currently there are available several methods for the assessment of body composition in adolescent athletes (Claessens et al;Malina et al, 2004;Malina, 2007;Malina & Geithner;Lohman et al;Slater et al), however due to the low time required, low cost and practical aspects, the anthropometry is one of the most used methods for the evaluation of the external morphology of various populations of adolescents, including young athletes (Claessens et al;Malina, 2007;Lohman et al;Slater et al). In young athletes, low levels of fat are generally observed (Malina, 2009;Malina & Geithner, 2011), including lower adiposity measured through skinfolds, lower body mass index (BMI) and lower percentage of fat mass (Strong et al, 2005), influenced by the type of sport practiced (Malina & Geithner; Slater et al). There is a scarcity of studies that evaluate the changes in body composition associated with training in young boy and girl athletes.…”
Section: Introductionmentioning
confidence: 99%
“…The heights and weights of youth athletes in weight category sports such as wrestling and weight lifting are affected by competitive weight categories which obviously influence weight and also height [1][2][3][4][5]. Although mean weights tend to equal or exceed reference medians, the percentage body fat (% Fat) is lower than average in young male athletes with the exception of athletes specializing in track and field throwing events and the heavier weight categories in wrestling [6,7]. In contrast to body size and body composition, the available data for maturity status in male adolescent athletes indicate a trend towards average and advanced status relative to the chronological age in most sports; an exception is gymnastics [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Age-adjusted means for % Fat in sprinters, middle distance runners and jumpers approximated the reference while age-adjusted means for distance runners and general athletics were, respectively, below and above the re fe r ence based on densitometry. NIR estimates of % Fat for athletes in specific track and field disciplines were consistently higher than estimates for other samples of athletes of the same age range and in the same discipli nes based on densitometry, total body water, DEXA or BIA [16,17].…”
Section: Discussionmentioning
confidence: 99%